(untitled) (Revista de Artes Marciales Asiáticas, 2015)
The existing cultural interconnection between Iran and North India, which existed and developed over a long period of time, is known today as “Indo-Iranian” or “Indo-Persian”, which could be applied to the region, culture, literature, weapons and other spheres of intercultural interference. The cultural cooperation between these two countries was bilateral and marked by trade routes. This paper is aimed at analyzing the interrelation, similarities and differences between the martial and military cultures of India and Persia. More precisely, the article describes the field of individual training in military skills, methods of their acquisition and retention, as well as the usage of the related weapons. For this purpose, we carried out a comparative analysis based on historical sources as well as on contemporary literature on the topic. First, the paper focuses on general principles and weapon traditions in both cultures. The next section deals with a description of some techniques of Persian swordsmanship as described in Persian manuscripts. The next part describes some aspects of Indian swordsmanship. Then the last part describes some similarities and differences related to techniques of swordsmanship in both traditions. However, one should stress that although there are many extant Persian manuscripts on warfare and fighting techniques, no related Indian manuscripts have been found so far. This article is only at an intial stage of research.